Elementos traço em tecido hepático de tartaruga-verde (Chelonia mydas) coletadas na Bacia de Santos, Brasil - Sulato, Everton Tiago [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
As, Cd, Cr, Cu, Pb, Mn, Mo, Zn, Ni, Ba V and Hg concentrations in liver tissue of green turtles (Chelonia mydas) stranded on the Brazilian coast (n=506) were determined. The data was compared to occurrence registers (date, location) and biological characteristics (sex, age, stage of development and curved carapace length). Possible temporal influence of oil exploration and production activities was assessed. The mean concentration of Cd, Cu, Mn, Zn and Hg were the highest reported in liver for C. mydas in Brazilian coast. The mean concentration of the elements in decreasing order was Cu> Zn> Cd> Mn> As> Hg> Mo> Pb> V> Ni> Ba> Cr. Significant difference between the sexes was observed for Hg (males > females). This difference had not been previously observed in Brazil. Significant differences (p < 0.05) were observed in the mean concentrations of As, Cu, Pb, Mo and V between specimens in their first years of life and aged ≥ 11 years, which suggests relation with dietary shift during development. These results were corroborated by curved carapace length (CCL) data, wherein individuals residing in coastal areas (CCL > 50 cm) presented higher concentrations for Cu, Pb, Mo, Zn, Ba and V when compared to the ones at the oceanic stage (CCL < 30 cm). The opposite pattern was observed for As and Hg. Spatial autocorrelation was not observed for element concentrations. In the present study, a baseline concentration of 12 trace elements was stablished for liver tissue of C. mydas juveniles in Santos Basin, Brazil, at 95% confidence level (As = 9 ± 10; Cd = 25 ± 18; Cr = 0.12 ± 0.10; Cu = 207 ± 125; Pb = 0.7 ± 1.0; Mn = 12 ± 4; Mo = 1.0 ± 0.6; Zn = 147 ± 50; Ni = 0.3 ± 0.4; Ba = 0.2 ± 0.3; V = 0.7 ± 0.9; Hg = 2 ± 22 mg kg-1). Influence of oil and natural gas production activities on the concentration of the elements could not be stablished. However, it was observed an expressive influence of the individual’s development stage, highly related to feeding habits, in the concentration of analyzed elements.

As concentrações de As, Cd, Cr, Cu, Pb, Mn, Mo, Zn, Ni, Ba V e Hg em tecido hepático de tartarugas verdes (Chelonia mydas) encalhadas na costa brasileira (n = 506) foram determinadas. Os dados foram comparados em função das variáveis do registro de ocorrência (data, local) e do registro das características biológicas (sexo, idade, estágio de desenvolvimento e comprimento curvilíneo da carapaça). A possível influência temporal das atividades de exploração e produção de petróleo foi avaliada. As concentrações médias de Cd, Cu, Mn, Zn e Hg foram as maiores encontradas em tecido hepático de C. mydas coletadas na costa do Brasil. A concentração média dos elementos em ordem decrescente foi Cu > Zn > Cd > Mn > As > Hg > Mo > Pb > V > Ni > Ba > Cr. Foi observada diferença significativa nas concentrações de Hg em função do sexo (machos > fêmeas). Diferenças significativas para sexo não haviam sido observadas anteriormente no Brasil. Foram observadas diferenças significativas (p < 0,05) entre as concentrações médias de As, Cu, Pb, Mo e V entre os indivíduos nos primeiros anos de vida e com idade ≥ 11 anos, sugerindo relação com a dieta dos indivíduos durante as fases de vida. Estes resultados foram corroborados pelos dados obtidos a partir do comprimento curvilíneo da carapaça (CCC), em que indivíduos com comportamento costeiro (CCC > 50 cm) apresentaram maiores concentrações médias para Cu, Pb, Mo, Zn, Ba e V quando comparados com indivíduos com comportamento oceânico (CCC < 30 cm). O oposto foi observado para as concentrações médias de As e Hg. Não foi observada autocorrelação espacial para as concentrações dos elementos. No presente estudo, a linha de base da concentração de 12 elementos traço em tecido hepático de indivíduos juvenis de C. mydas na Bacia de Santos, Brasil foi estabelecida (Nível de 95% de confiança), sendo As = 9 ± 10; Cd = 25 ± 18; Cr = 0,12 ± 0,10; Cu = 207 ± 125; Pb = 0,7 ± 1,0; Mn = 12 ± 4; Mo = 1,0 ± 0,6; Zn = 147 ± 50; Ni = 0,3 ± 0,4; Ba = 0,2 ± 0,3; V = 0,7 ± 0,9; Hg = 2 ± 22 mg kg-1 . Não foi possível estabelecer relação entre as concentrações dos elementos e fontes de contaminação provindas das atividades de exploração e produção de petróleo e gás natural. No entanto, foi observada expressiva influência da fase de desenvolvimento, fortemente relacionada aos hábitos alimentares, na concentração de elementos analisados.
Trace elements in green turtle hepatic tissue (Chelonia mydas) collected in the Santos Basin, Brazil
Keywords: Sea turtle; Liver; Curved carapace length; Baseline concentrations; Metals; Tartaruga marinha; Fígado; Comprimento curvilíneo da carapaça; Concentração de linha de base; Metais